2006
DOI: 10.1128/iai.74.4.2338-2352.2006
|View full text |Cite
|
Sign up to set email alerts
|

The Host Defense Peptide Beta-Defensin 1 Confers Protection against Bordetella pertussis in Newborn Piglets

Abstract: Innate immunity plays an important role in protection against respiratory infections in humans and animals. Host defense peptides such as beta-defensins represent major components of innate immunity. We recently developed a novel porcine model of pertussis, an important respiratory disease of young children and infants worldwide. Here, we investigated the role of porcine beta-defensin 1 (pBD-1), a porcine defensin homologue of human beta-defensin 2, in conferring protection against respiratory infection with B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 59 publications
3
46
0
Order By: Relevance
“…(iii) Active immunization does not provide protection against infection with B. pertussis in newborn piglets. Piglets of both vaccinated and control groups were challenged with 2 ϫ 10 10 to 5 ϫ 10 10 CFU of live bacteria at 24 to 26 days of age as we described elsewhere (46)(47)(48). Piglets from either control or vaccinated groups displayed clinical symptoms, including mild fever, nasal discharge, nonparoxysmal cough, and breathing difficulties, as we previously showed (46,48).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…(iii) Active immunization does not provide protection against infection with B. pertussis in newborn piglets. Piglets of both vaccinated and control groups were challenged with 2 ϫ 10 10 to 5 ϫ 10 10 CFU of live bacteria at 24 to 26 days of age as we described elsewhere (46)(47)(48). Piglets from either control or vaccinated groups displayed clinical symptoms, including mild fever, nasal discharge, nonparoxysmal cough, and breathing difficulties, as we previously showed (46,48).…”
Section: Resultsmentioning
confidence: 88%
“…Piglets were anesthetized with isoflurane and intubated using a laryngoscope and an endotracheal tube, and bacteria (5 ϫ 10 9 CFU) were delivered through the tube at a level of 1.5 ml/lung craniodorsal to the bronchial bifurcation, as we have previously described elsewhere (44,46,47).…”
Section: Methodsmentioning
confidence: 99%
“…A recent study has shown expression of porcine b-defensin 1 was only present in tongue of newborn piglets, as distinct from a wider panel of tissues in 4-5-week-old pigs [41] . It was therefore o nterest to examine the correlation between this early localisation of b-defensin expression during embryogenesis and the tissue specific expression patterns observed in earlier studies [42,43] .…”
Section: Discussionmentioning
confidence: 97%
“…Also, all experimental animal species will have lifespan restrictions when testing durability of protection. Moreover, no model, not even the human, has disclosed a defined correlate or surrogate of protection for pertussis (Table 1) [12,18,22,[96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113].…”
Section: Expert Commentarymentioning
confidence: 99%